Pengaruh Budaya Literasi Sekolah Terhadap Minat Baca Siswa SD Inpres Antang I Kota Makassar - selinnia21 ulandari; Syamsul Alam; Siti Nurul Haliza; Waddi Fatimah (Jurnal Elementaria Edukasia, 2023)
School literacy culture has a vertical relationship with the quality of the nation. Literacy is a skill that must be possessed by every student.however, according to a survey conducted by PISA, it showed that a literacy culture had not yet become entrenched among elementary school students and resulted in very low interest in reading among students. Indonesia was ranked 74th out of 79 countries. This research is an ex post facto research that uses a quantitative approach and is located at SD Inpres Antang I, MakassarCity. This study aims to determine the influence of school literacy culture on students’ interest in reading at SD Inpres Antang I Makassar City. The samples in this study were grades IV and V with a total of 42 students using a sample random sampling technique. Data Collection methode and data collection in this study is to use a quastionnaire and documentation with data analysis using SPSS version 20. As for the inferential analysis, the result of the normality test for literacy are 0,189 and reading interest is 0,312 > 0,05 (normal distribution), the homogenity test result are 0,405 > 0,05(homogeneous), the linearity test result are 0,201 > 0,05, thus there is a linear relantionship between school literacy culture and students’ reading interest. The result of the hypothesis test showed a sig value of 0,001 with sig 0,001 criteria < 0,05 so theoretically and empirically stated that school literacy culture affected students’ reading interest in SD Inpres Antang I Makassar City. So, through the result of the analysis, it can be concluded that the culture of school literacy influences the reading interest of students at SD Inpres Antang I Makassar City.